Figurative Language and Imagery Analysis on “I Wandered Lonely As a Cloud” By William Wordsworth: Semantics Study - Chintiya Veronika; Ida Zuraida (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study’s aim is to analyze and examine the types figurative language and imagery that consist in the poem. The analysis used a descriptive qualitative research method. The data used were taken from I Wandered Lonely As A Cloud book by William Wordsworth. The result demonstrates that there are four types of figurative language occurs found; 23% occurrence of comparison, 10% occurrence of contradiction, 10% occurrence of correlations, and 16% occurrence of repetition figurative language. Also, there are two types of imagery found; percentage occurrence of visual imagery is 47% while kinesthetic imagery is 10%. According to the findings of this analysis, figurative language occurs frequently in the type of comparison for percentage of 23% and visual imagery with 47% occurrence.